Myeloid Sarcoma in the Sinonasal Cavity with Orbital Involvement: A Case Report - Fitriani, Dianli; Murti, Krisna; Eriza, Eriza (Indonesian Journal of Cancer, 2024)
Introduction: Myeloid sarcoma (MS) is a tumor mass that arises outside of the bone marrow area and is composed of either mature or not myeloid blasts of white blood cells. Acute myeloid leukemia (AML), chronic myeloid leukemia (CML) with an imminent blast crisis, and other underlying undiagnosed myeloproliferative disorders are frequently linked to MS, an uncommon disease. Without a history of leukemia, MS is difficult to diagnose and might be misdiagnosed for lymphoma or undifferentiated carcinoma. For patients, correct tissue diagnosis based on immunohistochemistry and histomorphology is important.Case Presentation: Here, we present a 27-year-old woman who had a surgical procedure in The Department of Otorhinolaryngology-Head and Neck Surgery with the chief complaint of right nasal congestion and growing right eye protrusion. A solid mass in the right sinonasal region with infiltration into the retrobulbar area was confirmed by a head computed tomography (CT) scan. Cells with small to medium-sized cells, finely distributed chromatin, tiny nucleoli, and sparse cytoplasm were examined under a microscope. These cells were grouped in diffuse, linear, or Indian file patterns. Microscopic examination revealed morphology of myeloid tumor. Immunohistochemistry analysis emphasized the diagnosis of myeloid sarcoma. The patient then had chemotherapy, comprising of six cycles of docetaxel and carboplatin. After completing chemotherapy, a reduction in the size of the tumor mass was observed.Conclusions: MS was diagnosed based on histological, radiographic, and immunohistochemical studies. Additional immunohistochemistry analysis testing is necessary to rule out a number of differential diagnoses when diagnosing MS in patients without a history of leukemia or hematological malignancy. The positive expression of myeloid markers such as CD68, CD15, CD33, and CD34 supports a diagnosis of MS.